Geospatial differences among natural regions in the utilization of maternal health care services in India - Anil Jagan Hiwale; Kailash Chandra Das (Elsevier, 2022)
Background: The chances of a woman dying or becoming disabled during childbirth are closely connected to her socioeconomic status, cultural norms and values, and her home's geographical remoteness. Most of the studies were undertaken to address the issue of accessibility of the hospital's location and its impact on utilization of maternal healthcare utilization. Some studies also attempted to understand the pattern of utilization of healthcare utilization according to administrative and political regions. Objectives: This study aims to identify the Geographical differences in the utilization of maternal health services in India according to geographical regions, caste, religion, wealth status, and place of residence. Data and methods: Data for analysis was taken from the National Family Health Survey-4 (2015-16). Data management and analysis were performed using statistical software Stata 13.0. To identify the regional differences in the use of maternal healthcare services, study used the 75 th round of NSS's classification of India into 88 natural regions. Regional variations in the usage of maternal health care were plotted using ArcGIS 10.5, and the bivariate method. Results: Results shows that the utilization of partial ANC ranges from 33.8% to 91.9%. Utilization is lowest in the Northern Kerala region (33.8%) and, in ascending order, higher in Lakshadweep (34.4%), Goa (36.2%), Puducherry (43.1%), Southern Kerala (43.4%), Inland Tamil Nadu (44.5%), and Andaman and Nicobar Island (46.2%), the mountainous region of Jammu and Kashmir (46.7%), Coastal northern Tamil Nadu (49.9%) and Eastern Maharashtra (51.6%). Institutional delivery was the highest in Northern Kerala (100%) and lowest in the Nagaland (35.7%). Near-universal institutional delivery was also found in Southern Kerala (99.9%), Puducherry (99.9%), Coastal Northern Tamil Nadu (99.6%) and Lakshadweep (99.2%). Conclusions: Differences in the utilization of MCHS by women can be seen among India's natural regions. Utilization is lagging in the Himalayan Mountain ranges, areas with dense forest cover, the Ganga and Brahmaputra plains, and the Desert region of Rajasthan.